Learning for All : Towards Quality Education for Enhanced Productivity and Economic Growth in Indonesia - Fasih, Tazeen; Afkar, Rythia; Tomlinson, Heather (World Bank, Washington, DC, 2018)
This note synthesizes the findings of various analytical pieces conducted by the World Bank in the education sector in Indonesia. The World Bank has supported the knowledge base on education in Indonesia through several studies and technical assistance partnerships, which are noted at the end of this brief. The studies investigate various sub-sectors of education to effectively analyze critical issues in depth and recommend policy options.